SELECTION OF UNDERGRADUATE STUDENTS FOR ELITE ENGINEERING EDUCATION - Mikhail G. Minin; Natalia S. Mikhaylova; Daria S. Denchuk (Высшее образование в России)
This paper analyzes the results of research carried out in 2004-2015 to select students for training in the supplementary program of Elite Engineering Education (EEE) of Tomsk Polytechnic University. The authors have designed an admission test system using psychological and pedagogical criteria that predict students' success in learning natural sciences and mathematics, which are the fundamentals of engineering invention. The article provides an overview of students’ personal and professional competence development within the EEE Program in Tomsk Polytechnic University, as well as procedures and criteria used to measure it, and provides a comparison of the resulting values with those of the students of traditional programs. The article addresses the integrated approach in training bachelor's degree students for creative professional activity on the basis of engineering invention, as exemplified by the Elite Engineering Education Program implemented at National Research Tomsk Polytechnic University.